(untitled) (Journal of the College of Basic Education, 2022)
Abstract : The play of the child is one of the most important educational and educational means that has a role in delivering symbols to the child. The function of the uniform is combined with the symbolic symbols that it performs through its workings, which will leave the same child to respond to the costumes and to make the actor’s costume a material for creating and creating the aesthetic costume The theater is not only based on the representation of the subject, but on its creation or construction so that it shows that on stage an art work integrated and unified. The researcher mentioned in the first chapter the objectives of the research and presented the importance of the symbol in the theater of the child through the transfer of ideas and meanings to the child form and color in the sample research. The researcher explained in the theoretical framework, in the first section symbolic signs and transformations in the costumes of the theater of the child, the second section is the activity of code and coding in children’s theaters. The third chapter included the research community in the analysis of a single sample for the presence of the symbol in the format of the child’s theater. The researcher used the descriptive analytical approach in dealing with the sample And then collected the results of the researcher in Chapter IV and some conclusions and recommendations.